DESIGN AN INFORMATION SYSTEM PENDAWA BULUCINA (RAM) WEB-BASED USING THE WATERFALL METHOD - Rahel Marianti Ritonga; Ibnu Rasyid Munthe; Iwan Purnama (Jurnal Mantik, 2022)
Many types of businesses currently use information technology media in the form of applications such as the use of software applications (SOFTWARE) on the weighbridge in RAM Pandawa Bulucina in order to make it easier for palm fruit owners and admins or operators who are in their offices to assess transaction reports. This built application, created using Tools such as Visual studio code as a text editor, php and mysql as a programming language and Database by being designed with a simple flow and interface design using design methods including, context diagram design, data flow diagram as other designs that explain the flow of the application.